If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + 4b = 0 Combine like terms: 5b + 4b = 9b 9b = 0 Solving 9b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '9'. b = 0 Simplifying b = 0
| 1-20-6= | | 4z+5-z=8+2z-6 | | 9k^2-3+59=0 | | 111-5x=3x+15 | | -12+39= | | 0-5x=8-7x | | -25-2= | | 12-17= | | t^2-8t+22= | | -2(g-1)=g-4 | | 8-12= | | 2x^2=200 | | 7+4x=19+x | | 12b^2+3=0 | | 41-6x=3x+18 | | 13-8x=103-43x | | -165-10x=10x+15 | | 12c+99=33 | | -9w+8=35 | | 2n^2+5n-18=0 | | t^2-8t+22=0 | | 6x+11=83-2x | | -55=3x-112 | | 3x^2+14=-19 | | 5x^2+80=0 | | 6+8x=83+x | | 5x^2+8xy+5y^2-3=0 | | 8y-5+2y=70 | | 11x*11x=0 | | x^2-11x+13=0 | | 2x^3-3x^2-12x-11=0 | | -2(-4b-2)-7(b-3)=20 |